2018
DOI: 10.4067/s0717-95022018000200493
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perceptions and Usage of Short Anatomy Videos: A Preliminary Study

Abstract: STRKALJ, G.; HULME, A.; EL-HADDAD, J.; LUO, K.; CRAFFORD, D. & RAMPE, M. Students' perceptions and usage of short anatomy videos: A preliminary study. Int. J. Morphol., 36(2):493-499, 2018. SUMMARY:The efficacy of videos in anatomy education is still being debated. It appears that one of the major factors discouraging learners to use videos has been their length. To counteract this, 24 short videos (the longest lasting 1 minute and 13 seconds), were created for a course on musculoskeletal anatomy. Videos focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
8
0
2
Order By: Relevance
“…The investigators used self recorded videos, ranging from 14 s to 1 min 13 s, to identify muscles of the limbs and their relations by area. They reported that the shortness of the videos made them easy accessible to the students and that they could use them repeatedly [ 19 ]. Most students valued the presence of an instructor during (83%) (236/284) and after (85%) (241/284) watching the videos.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigators used self recorded videos, ranging from 14 s to 1 min 13 s, to identify muscles of the limbs and their relations by area. They reported that the shortness of the videos made them easy accessible to the students and that they could use them repeatedly [ 19 ]. Most students valued the presence of an instructor during (83%) (236/284) and after (85%) (241/284) watching the videos.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons and many more, some researchers, educators, and even students believe that using dissection alone is insufficient to learn anatomy, and that incorporating other educational tools is advantageous, or even required [ 7 , 16 18 ]. It is interesting to note that the use of additional educational resources is not exactly a brand new concept, since “motion picture” tools have been utilized since as far back as the 1970 s in the form of VHS tapes that then progressed to CD Roms and eventually the multiple video tools that are available today [ 19 ]. While the debate is still ongoing, many medical schools have opted to put dissection on hold due to the increased number of students, the shortage of time, cadavers, and qualified staff.…”
Section: Introductionmentioning
confidence: 99%
“…Their students performed dissections and used prosected bodies, also incorporating anatomical variations research that included dissections, histological techniques, imaging, and other activities (Kagan, 2002). There has been a clear shift in medical education around the world from a traditional teacher-centered education to a student-centered education, in which technology and innovation play a major role (Pawlina, 2009;Tam et al, 2009;Papa and Vaccarezza, 2013;Singh and Kharb, 2013;Strkalj et al, 2018). Studies from Latin American countries and Spain have reported the implementation of technological tools in medical education (Cotta, 2012;Tay et al, 2014;de Faria et al, 2016;Nuñez Ricardo, 2017;Cabrera et al, 2019;Tiznado-Matzner et al, 2019).…”
Section: Gross Anatomymentioning
confidence: 99%
“…The use of integrated curriculum continues to prevail in the improvement and efficacy of medical education, in combination with new interactive and technologic approaches (Drake et al, 2009). With the tendency to reduce the total number of hours (Drake et al, 2009), anatomical courses have included different pedagogic techniques (Elizondo‐Omaña, 2004; Sugand et al, 2010; Losco et al, 2017), problem‐based learning (Huitt et al, 2014), a clinical approach (Leveritt et al, 2016; McBride and Drake, 2018), review of imaging studies (Grignon et al, 2016), use of ultrasound (Sadler et al, 2018), online platforms (Vázquez et al, 2007), videos (Jaffar, 2012; Barry et al, 2016; Strkalj et al, 2018), virtual and augmented reality (Dee and Meyerholz, 2007; Petersson et al, 2009; Wilson et al, 2016; Moro et al, 2017), and three‐dimensional (3D) modeling/printing (Vernon and Peckham, 2002; Smith et al, 2018), among others. Each school appears to have implemented the methods that best align with their objectives and their available resources.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there exists little information on chiropractors' perceived relevance and adequacy of their anatomy education to their clinical practice. Previous research exploring pre-professional anatomy education within chiropractic programs confirmed considerable investment in anatomy teaching resources [8,11,13] but provided little insight into chiropractors' perceptions of the usefulness of these teaching tools. Determining chiropractors' perceptions of these tools will assist to develop anatomy curricula appropriate for chiropractic clinical practice.…”
Section: Introductionmentioning
confidence: 99%